If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(v + 7) = 6 + 4v Reorder the terms: -7(7 + v) = 6 + 4v (7 * -7 + v * -7) = 6 + 4v (-49 + -7v) = 6 + 4v Solving -49 + -7v = 6 + 4v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-4v' to each side of the equation. -49 + -7v + -4v = 6 + 4v + -4v Combine like terms: -7v + -4v = -11v -49 + -11v = 6 + 4v + -4v Combine like terms: 4v + -4v = 0 -49 + -11v = 6 + 0 -49 + -11v = 6 Add '49' to each side of the equation. -49 + 49 + -11v = 6 + 49 Combine like terms: -49 + 49 = 0 0 + -11v = 6 + 49 -11v = 6 + 49 Combine like terms: 6 + 49 = 55 -11v = 55 Divide each side by '-11'. v = -5 Simplifying v = -5
| 0.40x+0.15(120-x)=0.25(120) | | 7m+6-7+5+m-4= | | 13-3b=5(7b-5) | | 12x^2+12=25x | | -6+4x-2x-3+5x= | | 9x-(4x-17)=52 | | [9x-9]=7 | | 5w^2+27w+28=0 | | 6+4x=3(4+2x)+6 | | 3X+5=66-3X | | 5t+4+2t-6t=6+2 | | -36-6n=-3(n+8) | | 0.12-0.03(x+3)=-0.04(1-x) | | 2-2(3x-1)-1=4 | | -4(1+8x)=-4-4x | | 7x+3=-3x-5 | | 13+n/(-7)=0 | | 13+n/(-7)= | | -3p+8=6-(7p+5) | | 25x+4=5 | | v^2-9v=0 | | (5x+5)= | | -2x(4+3x)=6-4x | | 0.12-0.03(x+3)=0.04(1-x) | | 8+-3x=7x+8 | | 6(x+5)+4=48 | | -7v+2=-9(v+2) | | 2x+23=-3(2x-1) | | 15-[3+7y-4(y+4)]=-4(3y-6)-[9(y-1)-15y+14] | | 3x-14x+25=2-6x-12 | | 36x-1=-8 | | 9+6x-8=6x+33-4x |